Biomechanical Examination of Osseointegration of Titanium Implants Placed Simultaneously With Allogeneic Bone Transfer. Issue 1 (20th July 2021) - Acikan, Izzet; Dundar, Serkan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The aim of this study was to conduct a biomechanical analysis of the early period bone-implant connection of titanium implants in the same type of subjects. In this study, 18 Sprague Dawley rats were used. Four rats were killed to provide the allogeneic bone before the experiment, and the remaining were divided into a control group and an experimental allogeneic bone transfer group. Titanium machined surfaced implants were integrated in tibias in the controls and in the experimental group; simultaneously, implants were integrated into allogeneic bone in the bone transfer group. All the rats were sacrificed 14 days later. Bone tissues with titanium implants were removed for biomechanical analysis, which found that the resistance to force of the control group and the allogeneic graft group was 2.04 and 2.00 Newtons, respectively, and there was no significant difference between the two groups at 14 days, although numerically a higher figure was detected in the controls ( P > 0.05). It was concluded, within the limitations of this study, that an allogeneic bone transfer can be used as an alternative to an autogenous graft.